Cryoinjury-induced acute myocardial infarction model and ameroid constrictor-induced ischemic heart disease model in adult micro-mini pigs for preclinical studies. Issue 1 (December 2017) - Hirano, Akinori; Fujita, Jun; Kanazawa, Hideaki; Kawaguchi, Shinji; Handa, Noriko; Yamada, Yoshitake; Okuda, Shigeo; Hishikawa, Shuji; Teratani, Takumi; Kunita, Satoshi; Tohyama, Shugo; Seki, Tomohisa; et al.
Abstract Background Coronary artery diseases (CAD) are the most commonly occurring disorders in the developed countries. Development of new therapeutics and their success in clinical studies require confirmation of therapeutic effects in large animal models. Swine is an ideal animal model because their anatomical features are similar to humans. However, sometimes their large body size hampers translational research, particularly in cell or tissue transplantation procedures for adult stage and long-term observation studies. We have been developing the smallest experimental pig, called micro-mini pigs (MMPs), for regenerative medicine. Methods Five- to 14-month-old mature MMPs were used (n = 15, body weight: 13.4 ± 2.14 kg). In the acute myocardial infarction (AMI) model, AMI was induced by cryoinjury (CI). In the ischemic heart disease (IHD) model, IHD was induced using an ameroid constrictor (AC) that was applied to the left anterior descending artery, with the diagonal branches ligated. Cardiac function in both models was assessed by magnetic resonance imaging (MRI) with late gadolinium enhancement, and coronary angiography (CAG) was performed to evaluate the collateral arteries. Animals were sacrificed 4 weeks after procedures to evaluate the pathological changes. Results On MRI, the ejection fraction in CI-induced AMI models decreased from 57.7 ± 3.2% to 35.8 ± 4.7% (Δ62.2%, p = 0.012) (n = 8). In contrast, AC also impaired cardiac function, but some pigs did not develop heart failure due to the development of collateral branches (pre: 54.4 ± 4.4%, post: 41.1 ± 8.0%, Δ75.7%, p = 0.028 [n = 7]). Gadolinium contrast-enhanced MRI and pathological examination confirmed scarring in both models. The proportion of scar area in the left ventricular region of CI-induced AMI models vs. AC-induced IHD models was 19.4% vs. 10.3% (p = 0.046) (MRI) and 17.6% vs. 9.2% (p = 0.046) (pathology). Immunohistological analysis also showed the presence of marked neovascularization in AC models, which led to greater variation in the impairment of cardiac function. Conclusions MMPs are the smallest available swine for experimental use that are suitable for translational research. They allow for long-term observation of adult pathology. Both models of AMI and IHD were successfully established in MMPs. The MMP preclinical heart failure model may accelerate further development of new treatments for CAD.